PETER’S ANOMALY - Rares, Laya (UNIVERSITAS SAM RATULANGI, 2011)
Abstract: Peter?s anomaly is a congenital corneal anomaly characterized by central or paracentral opacity. Around 60-80% of this anomaly is bilateral. We reported a girl of one year and six months as having bilateral corneal opacity since she was born. Diagnosis was based on ophthalmological examinations: the vision of the right and left eyes was ?fix and follow the light?; sensoric nystagmus of both eyes; intra-ocular pressure of the right eye 37 mm Hg and of the left eye 40 mm Hg; corneal diameters of both eyes were 11 mm; 5-mm-central opacity of both cornea; both eye movements to all directions were normal; anterior chambers were shallow; iris was attached to the corneal endothelium; both lenses were difficult to be evaluated due to corneal opacity; fundal reflexes in both eyes were negative. The early medication given was thymolol 0.5% to decrease the intra-ocular pressure. If her health condition improved, a penetrating keratoplasty and a filtration surgery were recommended under general anaesthesia. Key words: Peter?s anomaly, corneal opacity, intraocular pressure, management. Abstrak: Peter?s anomaly merupakan kelainan kongenital kornea yang ditandai dengan kekeruhan pada kornea bagian sentral ataupun parasentral. Sekitar 60-80% kasus Peter?s anomaly terjadi bilateral. Kami melaporkan kasus Peter?s Anomaly pada seorang anak berusia satu tahun enam bulan dengan kekeruhan pada kedua mata sejak lahir. Diagnosis ditegakkan berdasarkan pemeriksaan oftalmologis dimana didapatkan visus okuli dekstra dan sinistra fix and follow the light, nistagmus sensoris pada kedua mata, tekanan intra okuler pada mata kanan 37 mm Hg dan pada mata kiri 40 mmHg. Diameter kornea kedua mata 11 mm, adanya kekeruhan pada sentral kornea (stroma) dengan diameter 5 mm pada kedua mata. Pergerakan kedua mata ke semua arah normal. Bilik mata anterior dangkal, iris melekat pada endotel kornea, lensa kedua mata sukar dievaluasi oleh karena kekeruhan pada kornea. Refleks fundus negatif pada kedua mata. Penanganan awal yang diberikan berupa medikamentosa (timolol 0,5%) untuk menurunkan tekanan intra okuler sambil menunggu keadaan umum membaik untuk dilakukan penetrating keratoplasty and filtration surgery dibawah anastesi umum. Kata Kunci: Peter?s anomaly, kekeruhan kornea, tekanan intra okuler, penanganan.